Dynamics in the Financial Markets of Europe in the Reflection of Streaming Financial Futures - Lyashenko, V.; Stepurina, S.; Novikova, T. (IJAAFMR, 2022)
Financial data plays an important role in economic development. These data determine the direction and dynamics of the relevant financial flows, which are one of the foundations of interaction between various business entities. The formation of such data occurs under the influence of the relevant processes of economic dynamics, which are manifested in various segments of t he financial market. One of the tools for such formation of data and the corresponding financial flows are financial futures. Based on this, the paper considers the dynamics of the main financial futures of the European financial market. The visualization of the dynamics of quotations for financial futures in the form of corresponding charts is presented. The main statistical characteristics of the dynamics of quotations for financial futures of the European financial market are summarized. The mutual dynamics of quotations for some pairs of futures that we analyze are considered. This allows you to choose the best investment strategy for entering the relevant segment of the financial market, to understand the dynamics of its development. For such an analysis, wavelet coherence estimates are used. The paper presents a lot of factual material in the form of graphs and diagrams, which helps to understand the logic of this study and its results.
Keywords: financial market; wavelet coherence